Analysis of the Additive Ratio Assessment Method in the Selection of the Best Production Head - Akbar Idaman; Amrullah; Vicky Rolanda (Jurnal Informasi dan Teknologi, 2024)
The selection of the Head of Production is crucial for ensuring the operational and strategic success of a company. This study employs the Additive Ratio Assessment (ARAS) method to provide an objective and structured approach to evaluating candidates for this key position. The ARAS method integrates various criteria, both qualitative and quantitative, to facilitate a comprehensive assessment. The research identifies relevant criteria, applies the ARAS method to evaluate candidates, and assesses the effectiveness and efficiency of this method in decision-making. The final results indicate that Head of Production 3 achieved the highest rank with a score of 0.104, demonstrating the best qualifications and capabilities for the position. Consequently, Head of Production 3 is deemed the most suitable candidate, expected to enhance the company's operational performance and success. This study contributes to the literature on the application of the ARAS method in employee selection and provides practical guidelines for companies to improve their selection processes.